Implementation of the Effect of Price and Service Quality on Honda Car Purchasing Decisions in Tegal (Case Study of PT. Dova Putra Manunggal Sejati) - Sri Undartik; Arie Nastio Reza; Khalid Iskandar; Fitriana Kartika Sari (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
To maintain a good name in the eyes of its customers, a company competes in terms of service or price. A good and reliable payment system will increase the number of buyers, making it easier for business actors to achieve their goals to get maximum profit. Not only that, the price also carries a markup that is specifically related to customer complaints. The term "price" refers to any form of monetary compensation that consumers may use to evaluate, obtain, and utilize various combinations of goods and services from a single product. A product is anything that can be sold at a discount to be noticed, bought, used, or consumed and that can satisfy a need or tendency. Regardless of the form a product takes when it is manufactured, a company's level of customer service is an important issue. The purpose of this study was to understand the relationship between price, product quality, and customer service in relation to purchase intent. The focus of the study was approximately 1,894 consumers who purchased Honda vehicles in 2021. The data analysis methodology uses segregated regression analysis. By performing the Instrumental Test and the Classical Assumption Test, the study findings show that price, product quality, and customer service, whether occurring simultaneously or sequentially, have a significant influence on buyer intent.